A heuristic study of the similarities and differences in offender characteristics across potential and successful serial sexual homicide offenders. (24th March 2021) - Yaksic, Enzo; Harrison, Marissa; Konikoff, Daniel; Mooney, Robyn; Allely, Clare; De Silva, Raneesha; Matykiewicz, Brenna; Inglis, Melissa; Giannangelo, Stephen J.; Daniels, Steven; Sarteschi, Christine M.
Abstract: This heuristic study examined potential serial sexual homicide offenders (SSHOs), an unacknowledged offender group comprised of aspiring and probable SSHOs, and compared them with successful SSHOs. Data were collected on six aspiring SSHOs who each failed a single homicide attempt, 16 probable SSHOs who committed 17 homicides in separate events, and 13 successful SSHOs who killed 90 victims in separate events. The study results indicate that while potential SSHOs share more in common with successful SSHOs than they do with single‐victim nonsexual homicide offenders, and that there is an overlap between potential SSHOs and successful SSHOs, there is currently insufficient evidence to suggest that there are discreet transitions among categories. While few potential SSHOs strive to become successful SSHOs, this may be due to weak or nonexistent emotional triggers. Being a potential SSHO does not appear to be a predictable first step on a pathway towards becoming a successful SSHO, as potential SSHOs cannot reliably be thought of as prospective SSHOs if all things were equal. The present study could not foresee all potential SSHOs becoming successful ones. An as yet unidentified number of factors still appear to separate potential SSHOs from successful SSHOs.